Blockchain and fintech technologies in the digital space of financial and industrial companies - Domashenko, Svitlana; Hres-Yevreinova, Svitlana; Zadoia, Yurii; Starostenko, Dmytro; Salin, Serhii (Sustainable Engineering and Innovation, 2023)
The relevance of the article lies in examining the functional relationship between blockchain and fintech technologies in the innovative digital space of financial and industrial companies. The research aims to investigate the directions for the development of large integrated systems of financial and industrial capital, based on the principles of intensive production. The research methodology included the following methods: analytical (literature review, quantitative analysis), methods of comparison, generalization, and systematization. In particular, quantitative analysis was applied to calculate the index of digital cyber protection, which serves as an indicator and summarizes the safe properties of information resources in the digital space of banking institutions and their ability to prevent cyber-attacks on the financial and industrial capital of subjects in united spheres of economic activity. The results of the research have shown that the optimal criteria for the index of digital cyber protection are financially linked to industrial capital. The article substantiates the macroprudential policy of Ukraine’s banking sector based on blockchain regulators and fintech technologies from the EU, which foster the intensive development of technological competitiveness among financial institutions. The article can be useful for financial and industrial executives, banking institutions, consulting firms, and educators seeking insights into the integration of blockchain and fintech technologies.